Understanding Usury and Its Influence on Interest in Using Bank Syariah Indonesia (BSI) Products: Case Study in Beganding Village - Br Sitepu, Himmatul Ulia; Rahmayati, Rahmayati (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to determine the effect of understanding of usury on the interest in using Bank Syariah Indonesia (BSI) products among Aisyiyah mothers in Beganding Village. Public understanding of the concept of usury is an important factor in encouraging participation in the Islamic banking system, which is based on Islamic financial principles. This study uses a quantitative approach with data collection techniques through questionnaires, which were distributed to 30 respondents. Data analysis was carried out using SPSS software. The results showed that understanding of usury had a significant effect on interest in using BSI products, with a calculated F value of 93.715 and a significance of 0.000 (p <0.05). The correlation coefficient value of 0.877 and the R² value of 0.770 indicate that 77% of the variation in interest can be explained by the variable of understanding usury. This finding indicates that the better a person's understanding of the prohibition of usury in Islam, the higher their interest in using Islamic banking services. This study provides academic contributions to the field of Islamic economics by emphasizing the importance of education related to usury as a strategy to increase literacy and participation in the Islamic banking industry at the community level.Keywords: Understanding of Usury; Interest in Using Products; Bank Syariah Indonesia.